Prevalence, sensitivity, and specificity of chronic cerebrospinal venous insufficiency in MS - Zivadinov, R; Marr, K; Cutter, G; Ramanathan, M; Benedict, R H B; Kennedy, C; Elfadil, M; Yeh, A E; Reuther, J; Brooks, C; Hunt, K; Andrews, M; et al. (Neurology, 2011)
Chronic cerebrospinal venous insufficiency (CCSVI) was recently described in patients with multiple sclerosis (MS). A subject is considered CCSVI positive if ≥ 2 venous hemodynamic (VH) criteria are fulfilled. To determine prevalence of CCSVI in a large cohort of patients with MS, clinically isolated syndrome (CIS), other neurologic diseases (OND), and healthy controls (HC), using specific proposed echo-color Doppler (ECD) criteria. Transcranial and extracranial ECD were carried out in 499 enrolled subjects (289 MS, 163 HC, 26 OND, 21 CIS). Prevalence rates for CCSVI were calculated in 3 ways: first, using only the subjects for whom diagnosis was certain (i.e., borderline subjects were excluded); secondly, including the borderline subjects in the "no CCSVI" group; and finally, taking into account subjects who presented any of the VH criteria. CCSVI prevalence with borderline cases included in the "no CCSVI" group was 56.1% in MS, 42.3% in OND, 38.1% in CIS, and 22.7% in HC (p < 0.001). The CCSVI prevalence figures were 62.5% for MS, 45.8% for OND, 42.1% for CIS, and 25.5% for HC when borderline cases were excluded (p < 0.001). The prevalence of one or more positive VH criteria was the highest in MS (81.3%), followed by CIS (76.2%), OND (65.4%), and HC (55.2%) (p < 0.001). CCSVI prevalence was higher in patients with progressive than in nonprogressive MS (p = 0.004). Our findings are consistent with an increased prevalence of CCSVI in MS but with modest sensitivity/specificity. Our findings point against CCSVI having a primary causative role in the development of MS.